Minat Menghafal Al-Qur’an pada Kalangan Keturunan Arab Yaman di Jakarta - Rohman, Baeti (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This research aims to analyze the interest in memorizing the Qur'an among Yemeni Arab descendants living in Jakarta, with a case study at SMP IT Al-Khairaat Condet, East Jakarta. Using a qualitative approach, this study involves in-depth interviews and participatory observations with Yemeni Arab descendant students, the Principal, and Teachers. The results indicate that the interest of Yemeni Arab descendant students at SMP IT Al-Khairaat in memorizing the Qur'an is relatively high. This strong interest is influenced by several factors. First, there is a strong desire within the students to memorize the Qur'an. Second, there is strong support from their families. Various strategies have been implemented by SMP IT Al-Khairaat to enhance students' interest in memorizing the Qur'an. First, support from the principal and the foundation. Second, a close bond between students' parents and teachers. Third, improving students' cognitive abilities. Fourth, teachers' attention to students. This research is expected to provide deeper insights into the religious dynamics within the Yemeni Arab descendant community in Jakarta and to offer recommendations for the development of more effective Qur'an learning programs.